2015
DOI: 10.1017/s0021859615000660
|View full text |Cite
|
Sign up to set email alerts
|

Applying urine collected from non-lactating dairy cows dosed with dicyandiamide to lysimeters and grass plots: effects on nitrous oxide emissions, nitrate leaching and herbage production

Abstract: SUMMARYIn agricultural production systems, nitrogen (N) losses to the environment can occur through nitrous oxide (N2O) emissions and nitrate (NO3−) leaching. The objectives of the present study were to evaluate: (1) if urine excreted by non-lactating dairy cows pulse-dosed with dicyandiamide (DCD) and applied to lysimeters reduced N2O-N emissions and NO3−-N leaching on two soil types; and (2) if urine + DCD would increase herbage production over winter. Lysimeters were used to measure N2O emissions and NO3-N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In addition to direct application on grazing grass, DCD is also included in animal feed, enabling its excretion with urine into the environment, resulting in a more focused approach. [88,89].…”
Section: Nitrification Inhibitors Commonly Used In Agricultural Produ...mentioning
confidence: 99%
“…In addition to direct application on grazing grass, DCD is also included in animal feed, enabling its excretion with urine into the environment, resulting in a more focused approach. [88,89].…”
Section: Nitrification Inhibitors Commonly Used In Agricultural Produ...mentioning
confidence: 99%
“…There are currently no studies used by the IPCC to refine the EF 3PRP that use emissions reported from grazed herbs such as chicory. Although some studies did not report sward composition [181][182][183] , calculations were made from predominantly grass swards [184][185][186][187][188][189][190][191][192] , grass-clover [144,186,[193][194][195][196][197][198] or forage crops (e.g., barley, lucerne, or brassicas such as rape, Brassica napus, or kale, Brassica oleracea var. sabellica) [186,194,199] .…”
Section: Urine-patch N 2 O Emissionsmentioning
confidence: 99%